Local Government Examination Corruption and the Crisis of the Merit Principle in Thailand’s Public Personnel Administration - Mungdonkang, Pudcharapon (Thai Social Science Journal, 2026)
This article examines corruption in competitive examinations for the recruitment of local government officials and employees as a crisis of Thailand’s public personnel administration system. Alleged irregularities in local government examinations are used as a case study to assess their effects on the merit principle, equality, personnel quality, public service delivery, and public trust. The study employs documentary research based on legislation, official documents, reports issued by oversight agencies, and academic literature concerning merit-based recruitment and public personnel administration. The findings indicate that score manipulation, solicitation of benefits, brokerage networks, and interference with appointment procedures do more than confer improper advantages on certain candidates. Such practices replace selection based on knowledge and competence with money, influence, and patronage networks, thereby depriving competitive examinations of their legitimacy as a gateway to public office. Honest candidates incur financial costs, devote substantial time to preparation, and lose career opportunities, while the appointment of unqualified individuals may undermine the exercise of public authority, budget administration, and the quality of local public services. Entry into public office through corrupt means may also create incentives to seek improper benefits in order to recover expenses or repay the networks that facilitated the appointment. The article argues that responsibility must be differentiated among those who manipulate scores, offer or receive benefits, act as brokers, neglect supervisory duties, exercise managerial authority, or knowingly accept unlawful assistance, while protecting candidates and appointees who acted in good faith. The annulment of examination results or appointment orders should be based on proportionality, available evidence, and the good faith of each affected person. Appropriate remedies should include score re-examination, independent appeals, reimbursement, and protection of legitimately acquired rights. The article recommends separating duties throughout the examination process, establishing auditable score-tracking systems, imposing supervisory accountability, enabling candidates to access their examination data, creating independent review mechanisms, and dismantling brokerage and position-buying networks. These reforms are necessary to restore the merit system and rebuild public confidence in local government personnel administration.